Comparison of sample preparation methods for the identification of Staphylococcus Aureus by MALDI-FOF MS - Horváth, Brigitta; Peles, Ferenc; Bereczki, László; Széll, András; Sipos, Rita; Erős, Ágnes; Lovász, Csaba; Micsinai, Adrienn (Acta Agraria Debreceniensis, 2019)
Coagulase-positive staphylococci include 3 species, Staphylococcus aureus, S. hyicus and S. intermedius. Of these three species, S. aureus is the most well-known human pathogen. S. aureus is part of the human and animal normal microbiota, however, it is capable of producing several staphylococcal enterotoxins (SEs) that cause intoxication symptoms of varying intensity in humans after consuming contaminated food. Selective media which are used for the determination of coagulase-positive staphylococci from foods are not able to identify isolates at a species. With the MALDI-TOF MS technique, we can identify S. aureus cheaper and faster than by using molecular methods. This paper describes the results of the study of the presence of coagulase-positive staphylococci and S. aureus in many food products, and the application of three sample preparation methods: direct sample preparation, formic acid suspension and ethanol extraction.